Wednesday

October 1, 2014

October 1, 2014

Posted by **-** on Saturday, November 7, 2009 at 8:27pm.

can be written as:

tan(x-y) = (tanx - tany) / (1+ tanxtany)

- adv functions -
**Reiny**, Saturday, November 7, 2009 at 11:18pmwrite tan (x-y)

= sin(x-y)/cos(x-y)

= [sinxcosy - cosxsiny[/[cosxcosy + sinxsiny]

Now divide everybody by cosxcosy and it will all fall into place.

**Answer this Question**

**Related Questions**

advanced functions - Show that tanx = sinx / cosx can be written as tan(x+y...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Trigonometry - Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b...

Trigo - Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b in ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

maths - trigonometry - I've asked about this same question before, and someone ...

Mathematics - Trigonometric Identities - Prove: sinx + tanx = tanx (1 + cosx) ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

Math - Im really struggling with these proving identities problems can somebody ...

Trig (inverse functions) - Problem: tan[arccsc(-5/3) + arctan(1/4)] My work: let...